Effect of ionizing radiation towards human health: a review - Abu Bakar, Nurul Fathihah; Othman, Siti Amira; Nor Azman, Nor Farah Amirah; Jasrin, Nurin Saqinah (2018)
This paper reviews the properties, process and effect of ionizing radiation towards human health. Ionizing radiation is a radiation that carries enough energy to liberate electrons from atoms or molecules, thereby ionizing them. Ionizing radiation is made up of energetic subatomic particles, ions or atoms moving at high speeds such as alpha, beta, gamma, neutron particles and X-rays. The spontaneous disintegration of atoms is known as radioactivity and the excess energy emitted is a form of ionizing radiation. Unstable elements which disintegrate and emit ionizing radiation are called radionuclides. It has many beneficial applications, including uses in medicine, industry, agriculture and research. As the use of ionizing radiation increases, so does the potential for health hazards. Radiation exposure may be internal or external, and can be acquired through various exposure pathways. Different organs have different sensitivity to ionizing radiation. Understanding the effects of radiation on human bodies provide useful information for the development of radiation protection measures.